The Six Principles of Belom Bahadat: Decolonizing Sustainable Food Governance in Central Kalimantan - Tulis, Riamona Sadelman; Pramusinto, Agus; Subarsono, Agustinus; Kusumasari, Bevaola (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2026)
The National Strategic Food Estate Program in Central Kalimantan (2020–2024) failed to achieve its objectives not solely due to technical agricultural issues, but because state policy lost its footing in local institutions, knowledge, and community values. This article addresses one central question: how can indigenous values ​​be translated into governance mechanisms that restore the legitimacy and effectiveness of state food policy? Using qualitative case studies in Pulang Pisau, Kapuas, and Gunung Mas Regencies (May 2022–July 2025) through in-depth interviews, participant observation, focus group discussions, and document review, this research identified five consistent patterns of failure: centralized knowledge and one-way socialization, a ban on land burning without alternatives, technological assistance inappropriate to field conditions, a lack of community involvement in planning, and the neglect of ecological knowledge and customary institutions (Damang). This article then proposes six principles of Belom Bahadat of the Dayak Ngaju community as a procedural framework that links local values ​​with public administration functions: Pambelom (planning), Imbelom (coordination), Mambelom (implementation), Hakam (supervision), Kabelom (accountability), and Kabalumam Belom (social justice). Its theoretical contribution is bridging the study of collaborative governance and policy implementation with customary institutions; its practical contribution is an instrument that can be adopted by the bureaucracy through regional regulations, equal coordination forums, and customary law-based supervision. This article emphasizes that decolonizing food governance is essentially an effort to restore the coherence of state institutions so that policies are rooted in the values, culture, and needs of local communities.